Observing Palangkaraya Readiness as Indonesia's New Capital City from the Entrepreneurial Perspective - Saputra Adiwijaya; Pipit Anggriati Ningrum (Budapest International Research and Critics University, 2019)
The discourse of transferring the government capital to Palangkaraya city in recent years has been widely discussed with various studies until the central government also provides support so that this discourse is seriously studied. As a candidate for the capital city, Palangkaraya welcoms the discourse with a variety of preparations to support it, in turn that Palangkaraya that is truly ready to become a government capital of the Republic of Indonesia. One of the important studies to welcome the readiness of Palangkaraya city as the government capital of the Republic of Indonesia is from entrepreneurship, for business people who are members of the Small and Medium Industries (IKM) in Central Kalimantan Province has the hope that the potential of superior products is patterned locality can increase its competitiveness and in other parts community empowerment can continue to be sustainable.This paper aims to provide a scientific review that the readiness of Palangkaraya as the capital city needs to pay attention to the creative business units that have existed in the community through the potential of IKM that is ready to develop later.